2014
DOI: 10.15282/jmes.7.2014.16.0114
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Effects of MIG Welding on Corrosion Behaviour of AISI 1010 Carbon Steel

Abstract: This paper presents the corrosion behaviour of welded low carbon steel at different welding voltages and filler materials. The welding process was conducted on butt joint specimens using the metal inert gas (MIG) technique at a welding voltage range of 19 to 21 V with 1 V interval, and the filler materials used were ER 308L and ER 70S-6 with 1.2 mm diameter. Heat treatment through full annealing was done to the welded low carbon steel, and the corrosion behaviour was tested using a synthetic seawater environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Figure 5 shows the SEM analysis after 60 days of immersion in seawater. Other than that, corrosion was produced due to the exposure of the substrate after electrochemical testing [25]. By comparing the SEM images at the same magnification, it was observed that the surface was very rough and severely damage as shown in Figure 5, which represents the surface of specimen without inhibitor.…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Figure 5 shows the SEM analysis after 60 days of immersion in seawater. Other than that, corrosion was produced due to the exposure of the substrate after electrochemical testing [25]. By comparing the SEM images at the same magnification, it was observed that the surface was very rough and severely damage as shown in Figure 5, which represents the surface of specimen without inhibitor.…”
Section: Scanning Electron Microscopementioning
confidence: 99%
“…Mechanical load and environment in materials / areas can begin the occurrence of corrosion and can be pointed at the initial failure. The development of the electrochemical measurement is an important tool to understand the effects of stress corrosion [9]. Such understanding is important because previous researchers who have conducted research on stress corrosion cracking (SCC) are more focused on the occurrence of corrosion cracking, the speed of corrosion on the cracking and the corrosion effects on the crack propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The method of clamping and its effects on machine processes are well understood. Besides that, clamping claws is an easy and less costly system, however, it leads to varying temperature distributions which could be improved through the use of pressure bars [5][6][7]. Advanced research have indicated that continuous clamping approaches could lead to a more consistent FSW quality along the joint's length [8].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum 7075, along with the traditional welding techniques, is relatively a high strength material that can be used for highly stressed structural parts [30]. The widely available AA6061-T6 has a good workability, high resistance to corrosion, and excellent joining characteristics [31]. For instance, the FSW of these dissimilar alloys fully utilizes both materials [32,33].…”
Section: Introductionmentioning
confidence: 99%